Improving quality of life with a team approach: a case report - (:unkn) unknown (My University, 2001)
An adolescent female who presented amelogenesis imperfecta with severe anterior open bite, long face, facial asymmetry, high angle, and Class III skeletal pattern was treated with an interdisciplinary (orthodontics, orthognathic surgery, and prosthodontics) treatment approach. Presurgical orthodontic treatment was followed by surgical maxillary posterior impaction with anterior advancement and mandibular setback operation with vertical chin reduction and genioplasty. After the surgery, anterior ceramic laminate veneers and posterior full ceramic onlay-crowns were performed. The results showed that function and esthetics were achieved successfully with interdisciplinary collaboration.
Keywords: Female; Humans; Quality of Life; Adolescent; Esthetics, Dental; Maxilla; Orthodontics, Corrective; Open Bite; Mandible; Crowns; Dental Prosthesis Design; Dental Veneers; Malocclusion, Angle Class III; Facial Asymmetry; Patient Care Team; Amelogenesis Imperfecta; Inlays; Ceramics; Chin